A review of concussion diagnosis and management in Australian professional sporting codes - Gunasekaran, P.; Hodge, C.; Pearce, A.; King, D.; Fraser, C. (The Physician and Sportsmedicine, 2020)
Objectives: The recognition and management of concussion has become a major health concern across all sports. Despite recent attention, concussion assessment and return-to-play protocols appear to be highly variable between leading professional sporting bodies across Australia. Without readily available guidelines, players at all levels may be at risk of suboptimal management following in-game trauma. The purpose of this study was to explore the publicly available concussion guidelines of the major Australian sporting codes with an aim to identify potential opportunities to develop a national sporting consensus.